Health Care Indicators - Donham, Carolyn S. (CENTERS for MEDICARE & MEDICAID SERVICES, 1989)
Contained in this regular feature of the journal is a section on each of the following four topics: community hospital statistics; employment, hours, and earnings in the private health sector; health care prices; and national economic indicators.